2009
DOI: 10.3171/2009.5.jns09164
|View full text |Cite
|
Sign up to set email alerts
|

Cortical mapping and frameless stereotactic navigation in the high-field intraoperative magnetic resonance imaging suite

Abstract: Frameless stereotactic neuronavigation provides tracking of surgical instruments on radiographic images and orients the surgeon to tumor margins at surgery. Bipolar electrical stimulation mapping (ESM) delineates safe limits for resection of brain tumors adjacent to eloquent cortex. These standard techniques could complement the capability of intraoperative MR (iMR) imaging to evaluate for occult residual disease during surgery and promote more complete tumor removal. The use of frameless neuronavigation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…The rate of GTR achieved in our study is similar to the rates reported previously. 16,19,21,33,35 Although OS and PFS were different between the LGG and HGG groups, the relatively short observational period (a mean of 24.8 months) prevents us from making any definitive conclusion for the LGG group based on these results. Nonetheless, to our knowledge this is the first study to analyze the clinical outcomes, and the follow-up period is considerably longer than in the previous reports.…”
Section: Discussionmentioning
confidence: 76%
“…The rate of GTR achieved in our study is similar to the rates reported previously. 16,19,21,33,35 Although OS and PFS were different between the LGG and HGG groups, the relatively short observational period (a mean of 24.8 months) prevents us from making any definitive conclusion for the LGG group based on these results. Nonetheless, to our knowledge this is the first study to analyze the clinical outcomes, and the follow-up period is considerably longer than in the previous reports.…”
Section: Discussionmentioning
confidence: 76%
“…3,11,12,13,24 In the series described by Leuthardt et al 11 and the case report by Parney et al, 13 an overhead moveable magnet was used for scanning. However, in the other series, 3,12,24 including ours, the position of the magnet was fixed on the floor, and the patient was moved toward the scanner for intraoperative scans. The overall operative time in our patient population was 7.3 hours, which is longer than the times reported in the other published studies.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,[11][12][13][14]18,[22][23][24] In some earlier work we showed that intraoperative multimodality electrophysiological mapping can be seamlessly incorporated into high-field iMRI for tumor resections. 15 Initially when we started the procedure of combining awake craniotomy with high-field iMRI, there were a number of challenges to overcome, including patient comfort and position as well as new draping and anesthetic techniques unique to the iMRI environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of permanent deficit is approximately 5%, according to the largest series in the literature using subcortical white matter stimulation for perirolandic gliomas [9] . The safety of using electrophysiological monitoring in the intraoperative magnetic environment has recently been described [10,11] . The purpose of this report is to present the feasibility and advantages of integrating functional navigation and direct cortical and subcortical stimulation using a single monopolar probe.…”
Section: Introductionmentioning
confidence: 99%